Investigating a Suitable Ratio of Iron Ore Tailings and Quarry Dust in Concrete Production. - Kasozi, Mark (Kabale University, 2024)
Concrete is the most widely used construction material, man consumes no material except water in such a tremendous quantity. Concrete is a homogeneous mixture of cement, coarse and fine aggregates, and water which consolidates into hard mass due to the chemical reaction between the cement and water, but its production has significant environmental consequences, including high carbon emissions and natural resource depletion. As a result, there is an increasing interest in the development of sustainable concrete technologies that reduce concrete's environmental footprint while maintaining its performance and durability. Sustainable development is a development that meets the needs of the present without compromising the ability of future generations to meet their own needs. Iron ore tailings are the residual materials left over after the extraction of iron ore from its ore body on the other hand quarry dust is a fine-grained material produced as a by-product of quarrying operations. It is typically composed of crushed stone, sand, and other mineral particles. The main objective of this study is to investigate a suitable ratio of iron ore tailings and quarry dust in concrete production by determining the physical properties of fine aggregate, designing a concrete mix conducting mechanical tests, and conducting a comparative study between the effect of Buhara IOT and Ntungoma quarry dust. IOT gives a Cu of 6.3 and quarry dust a Cu of 7.5 and they are both greater than 4 implying that both are well-graded materials. Higher values of Cu imply that D60 is significantly larger than D10. This means that both larger and smaller particles a present in significant quantities. The fineness modulus of quarry dust is 3 and that of IOT is 3.5 implying that IOT has a higher percentage of coarse particles. IOT particles produced a higher density than both quarry dust particles and coarse aggregates combined. Quarry dust had a greater water absorption than iron ore tailings because it had more quantities of finer aggregates than iron tailings making it absorb more water. workability increased with an increase in the percentage of quarry dust and at 80% quarry dust and 20% IOT obtained the highest slump value of 35mm, Compressive strength increased with an increase in quarry dust percentages. Maximum percentage was obtained at 80% quarry dust and 20% IOT. At 28 days we obtained the maximum compressive strength of 19Mpa.